2020
DOI: 10.1631/jzus.b2000211
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study

Abstract: Background: Currently, there are no drugs that have been proven to be effective against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Because of its broad antiviral activity, interferon (IFN) should be evaluated as a potential therapeutic agent for treatment of coronavirus disease 2019 (COVID-19), especially while COVID-19-specific therapies are still under development. Methods: Confirmed COVID-19 patients hospitalized in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Such an approach was taken in a recent analysis of an uncontrolled exploratory study of nebulised interferon alfa-2b, reported in a hospital setting in Wuhan, China, indicating a positive effect on viral load and the inflammatory biomarkers interleukin-6 and C-reactive protein, although there was an imbalance in age between treated patients and controls. 28 , 29 More recently, a similar, pragmatic, open-label study reported clinical benefits with aerosol inhalation of interferon kappa plus trefoil factor 2, showing reductions in viral shedding and duration of symptoms and hospital stay in patients with SARS-CoV-2 infection. 30 Taken together with our study, these results suggest a potential antiviral benefit of aerosolised interferon therapy in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach was taken in a recent analysis of an uncontrolled exploratory study of nebulised interferon alfa-2b, reported in a hospital setting in Wuhan, China, indicating a positive effect on viral load and the inflammatory biomarkers interleukin-6 and C-reactive protein, although there was an imbalance in age between treated patients and controls. 28 , 29 More recently, a similar, pragmatic, open-label study reported clinical benefits with aerosol inhalation of interferon kappa plus trefoil factor 2, showing reductions in viral shedding and duration of symptoms and hospital stay in patients with SARS-CoV-2 infection. 30 Taken together with our study, these results suggest a potential antiviral benefit of aerosolised interferon therapy in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… [175] , [176] A case-control study presented varying results on the effects of IFNα inhalation in reducing viral shedding time and the length of hospitalization. [52] Patients treated with IFN-α2b inhalation had significantly shorter viral shedding time and hospitalization; however, statistical significance was lost after applying the propensity score matching method. Treatment was initiated for the IFNα group (which consisted of 41 mild, 22 severe, and 5 critically ill patients) at a median of 5 days (Q1-Q3: 3-8), and no difference in the timing of treatment initiation was found when compared with the control group.…”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsmentioning
confidence: 97%
“…A total of 178 studies were found to have reported IFNα treatment for COVID-19 (Supplemental 2). [13] , [17] , [19] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , …”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsunclassified
See 1 more Smart Citation
“…Another study using IFN-α2b via spray inhalation to 68 patients matched with 36 case controls, with both groups with PCR confirmed COVID-19, did not demonstrate reduced viral shedding but signaled shorter hospitalization times ( 83 ).…”
Section: Intranasal Interferons In Prevention and Treatment Of Viral ...mentioning
confidence: 99%